Variation in heart and blood lactate concentration in freestyle kytesurfing - Camps, A.; Vercruyssen, F.; Brisswalter, J. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM:The aim of this paper was to evaluate the physiological demands of freestyle kitesurfing. METHODS: Ten elite subjects performed an incremental running test on a treadmill and a three 7 min simulated freestyle heats of kitesurfing in MW (Midwind) condition ranging from 15 to 22 knots. Oxygen uptake (VO2) was estimated from the heart rate (HR) recorded during the freestyle trial using the individual HR-VO2 relationship determined during the incremental test. Blood lactate concentration [Lab] was measured at rest and 3 min after the exercise completion. 3 experienced kitesurfers acted as judges to better simulate competition conditions. RESULTS:Linear relationship was demonstrated between scores and % HRmax on water (r=-0.764, P<0.05), HRmax on water (r=-0.684, P<0.05) estimated VO2 on water (r=-0.724, P<0.05), HR on water (r=0.709, P<0.05), % VO2 on water (r=0.740, P<0.05), final [Lab] (r=-0.884, P<0.05), anaerobic threshold (AT) (r=0.836, P<0.05), HR in AT (r=0.748, P<0.05) and ranking (r=-0,924, P<0.05), mean HR and estimated VO2 values represented, respectively 85.4±3.0% of maximal heart rate and 80.0±4.5% of maximal oxygen uptake. Mid values for [Lab] were observed at the end of crossing trial (5.2±0.8 mmol/L). CONCLUSION:This first analysis of freestyle kitesurfing suggests that the energy demand is sustained by both aerobic and anaerobic metabolism during a MW condition and freestyle event of kitesurfing.